A comparative study on pain, anxiety level and vital signs during pre and post phacoemulsification using combination of tropical anaesthesia and binaural beats audio versus tropical anaesthesia - Loong, Ling Jiunn (2018)
Introduction: Topical anaesthesia has become a popular choice of anaesthesia during phacoemulsification as it has no risk of the needle techniques. Phacoemulsification performed using topical anaesthesia has acceptable pain control. However, a certain percentage of patients still perceive pain during the procedure. There are ongoing studies to find additions to the topical anaesthesia to increase patient’s level of comfort during phacoemulsification. Binaural beats audio is the usage of certain audio frequency wavelength to relief pain and anxiety. There is no reported data on the effect of usage of Binaural Beats audio as an adjunct to topical anaesthesia on pain and anxiety control during phacoemulsification so far. Objective: To evaluate the effect of Binaural Beats audio as an adjunct to topical anaesthesia on pain score, anxiety level and vital signs during phacoemulsification. Methodology: 61 patients with senile cataract planned for phacoemulsification who met the inclusion and exclusion criteria were recruited. Patients were randomised into two groups- topical anaesthesia only (control group) and topical anaesthesia with the usage of Binaural Beats audio (study group). Before the start of surgery, patient’s blood pressure, heart rate and anxiety level were assessed. Phacoemulsification was performed by a single Ophthalmologists. The group using topical anaesthesia only were given earphones without audio. The group using topical anaesthesia with usage of Binaural Beats audio were given alpha wave frequency through the earphones throughout the surgery. Patients rated intraoperative pain score immediately after the surgery. Patient’s blood pressure, heart rate and anxiety level were assessed again postoperatively. Result: Postoperatively, statistically significant reduction of pain score and anxiety level between groups were seen (p<0.05). Diastolic blood pressure, mean arterial blood pressure and heart rate at the end of the surgery were also lower in the study group (p<0.05). However, systolic blood pressure was comparatively lower postoperatively but was not statistically significant (p=0.068) Conclusion: Phacoemulsification using topical anaesthesia with Binaural Beats audio has significantly improved patient’s level of pain. Addition of binaural beats to topical anaesthesia still produces a safe systemic physiological stress response (anxiety level, blood pressure and heart rate).